Volume 1: Development and Characterization of Multifunctional Materials; Modeling, Simulation and Control of Adaptive Systems; 2014
DOI: 10.1115/smasis2014-7446
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization and Form-Finding of Cylindrical Shells for Targeted Elastic Postbuckling Response

Abstract: This paper presents a finite element based numerical study on controlling the postbuckling behavior of thin-walled cylindrical shells under axial compression. With the increasing interest of various disciplines for harnessing elastic instabilities in materials and mechanical systems, the postbuckling behavior of thin-walled cylindrical shells may have a new role to design materials and structures at multiple scales with switchable functionalities, morphogenesis, etc. In the design optimization approach present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A prior numerical study by Hu and Burgueño [9] found that there is a strong correlation between K i , DP max , and A. This observation is confirmed by the tests reported here.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A prior numerical study by Hu and Burgueño [9] found that there is a strong correlation between K i , DP max , and A. This observation is confirmed by the tests reported here.…”
Section: Resultssupporting
confidence: 90%
“…Prior studies by the authors [9][10][11][12] have shown that the elastic postbuckling response of cylindrical shells can be modified by providing large and strategically designed imperfections, namely, a seeded geometric imperfection (SGI). Specifically, the first paper [10] only presented the SGI concept as one of three approaches to modify the postbuckling behavior.…”
Section: Introductionmentioning
confidence: 99%
“…as a cylindrical rocket structure. Most promisingly, a research group at Michigan State University have shown that the elastic post-buckling response of cylinders can be modified by providing large and strategically designed imperfections [18,19,2,20,21,22] in the form of seeded geometric alterations.…”
Section: Introductionmentioning
confidence: 99%